IMPLEMENTASI KEARIFAN BUDAYA LOKAL PADA MASYARAKAT ADAT KAMPUNG KUTA SEBAGAI SUMBER PEMBELAJARAN IPS - Agus Efendi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article aims to provide an overview of the implementation of local wisdom in the indigenous community of Kampung Kuta as a source of social studies learning.The method used is ethnography and Classroom Action Research. The research showed that environmental wisdom as one of the growing cultural values in society are able to make Kuta remain sustainable natural environment. The values of local wisdom, particularly environmental wisdom, is very important to make learning more meaningful social studies. The significance of the values of local wisdom of Kuta indigenous peoples as a source of learning social studies is seen from the results of studies showing the presence of two important things. First, the interest and passion of learners have increased. Second, teachers and the book are no longer the only source of learning.